2020
DOI: 10.1371/journal.pone.0226688
|View full text |Cite
|
Sign up to set email alerts
|

Altered insulin-like growth factor-2 signaling is associated with psychopathology and cognitive deficits in patients with schizophrenia

Abstract: BackgroundSchizophrenia is linked with abnormal brain neurodevelopment, on which IGF-2 (insulin-like growth factor-2) has a great impact. The purpose of this study was to assess the levels of serum IGF-2 and its binding proteins IGFBP-3 and IGFBP-7 in schizophrenia patients and the associations of these proteins with schizophrenia psychopathology and cognitive deficits. -Q, et al. (2020) Altered insulin-like growth factor-2 signaling is associated with psychopathology and cognitive deficits in patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
4
24
4
Order By: Relevance
“…Language ability, executive function, attention, and the ability to lter irrelevant stimuli are all impaired. Working memory and executive function of patients with schizophrenia are also impaired [27][28][29]. Consistent with this nding, several cognitive de cits have been reported in adolescent schizophrenia.…”
Section: Discussionsupporting
confidence: 80%
“…Language ability, executive function, attention, and the ability to lter irrelevant stimuli are all impaired. Working memory and executive function of patients with schizophrenia are also impaired [27][28][29]. Consistent with this nding, several cognitive de cits have been reported in adolescent schizophrenia.…”
Section: Discussionsupporting
confidence: 80%
“…As one of the IGFs, IGF-2 is expressed in brains not only during the development period but also during adulthood [14] . Recent studies have demonstrated that alterations of IGF-2 signaling are implicated in the pathogenesis of schizophrenia [15][16][17][18] . Specifically, a large CommonMind consortium RNA-sequencing study revealed that IGF-2 was the top downregulated gene in the prefrontal cortex of patients with schizophrenia [15] .…”
mentioning
confidence: 99%
“…Altered IGF-2 expression was reported in various diseases. For example, it was shown that schizophrenia patients who are not taking any antipsychotic medication have a decreased serum IGF-2 concentration compared with healthy controls [ 17 ]. On the contrary, patients who had been receiving a stable dose of oral antipsychotic medications had increased serum IGF-2 level [ 18 ].…”
Section: Introductionmentioning
confidence: 99%